TEACHING OF BEHAVIORAL AND EXPERIMENTAL ECONOMICS AND THE PROSPECTS FOR TEACHING IT IN DEVELOPING COUNTRIES: A SURVEY - Muhammad Ryan Sanjaya (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
The rising trend of behavioral and experimental economics is observed through a survey of the top 100 academic institutions in economics and econometrics. The survey found that this subject is relatively popular with around 44% of academic institutions offering this course to undergraduate students. Another survey on publication interest found a surge since 2002 that was experienced by this subject along with only a few other subjects such as labor economics and business economics. Lastly, four short experiments on undergraduate students were conducted in Indonesia to explain economics, and this activity seems to support the studentcentered learning that has since became the focus of the Directorate General of Higher Education in Indonesia.